Downward transport of ozone rich air and implications for atmospheric chemistry in the Amazon rainforest. (January 2016) - Gerken, Tobias; Wei, Dandan; Chase, Randy J.; Fuentes, Jose D.; Schumacher, Courtney; Machado, Luiz A.T.; Andreoli, Rita V.; Chamecki, Marcelo; Ferreira de Souza, Rodrigo A.; Freire, Livia S.; Jardine, Angela B.; Manzi, Antonio O.; et al.
Abstract: From April 2014 to January 2015, ozone (O3 ) dynamics were investigated as part of GoAmazon 2014/5 project in the central Amazon rainforest of Brazil. Just above the forest canopy, maximum hourly O3 mixing ratios averaged 20 ppbv (parts per billion on a volume basis) during the June–September dry months and 15 ppbv during the wet months. Ozone levels occasionally exceeded 75 ppbv in response to influences from biomass burning and regional air pollution. Individual convective storms transported O3 -rich air parcels from the mid-troposphere to the surface and abruptly enhanced the regional atmospheric boundary layer by as much as 25 ppbv. In contrast to the individual storms, days with multiple convective systems produced successive, cumulative ground-level O3 increases. The magnitude of O3 enhancements depended on the vertical distribution of O3 within storm downdrafts and origin of downdrafts in the troposphere. Ozone mixing ratios remained enhanced for > 2 h following the passage of storms, which enhanced chemical processing of rainforest-emitted isoprene and monoterpenes. Reactions of isoprene and monoterpenes with O3 are modeled to generate maximum hydroxyl radical formation rates of 6 × 10 6 radicals cm −3 s −1 . Therefore, one key conclusion of the present study is that downdrafts of convective storms are estimated to transport enough O3 to the surface to initiate a series of reactions that reduce the lifetimes of rainforest-emitted hydrocarbons. Highlights: In the rainforest, convective storms transport ozone-rich air to the surface. Ozone levels remain enhanced for more than 2 h after the passage of storms. Enhanced ozone drives oxidation of rainforest-emitted hydrocarbons.